A new species and additional records of Pseudolathra Casey (Coleoptera: Staphylinidae: Paederinae) from southern China - Peng, Zhong; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2014)
Material of the paederine genus Pseudolathra Casey, 1905 from the Chinese provinces of Zhejiang, Shanghai, Hunan, Guizhou, Guangxi and Hainan is examined. Six species are identified, one of which is described: P. glabra Peng & Li sp. n. (Guizhou: Mayanghe). The genus is now represented in the Oriental and eastern Palaearctic regions by 29 species.